Tourism Sector Development Strategy Of Kalimantung Island And Mursala Island In Islamic Economic Perspective - Rodhiatul Aslamah Meuraxa; Azhari Akmal Tarigan; Marliyah Marliyah (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
One of the sectors that can support the increase in Regional Original Revenue (PAD), improvement of social life of the community and improvements to the marine environment is the tourism sector. However, the tourism sector in Central Tapanuli Regency has not been managed and utilized optimally, especially the tourism of kalimantung island and mursala island. The author focuses on the problem of the development strategy of the tourism sector of kalimantung island and mursala island and the many tourism assets in Central Tapanuli Regency that are still not managed properly and correctly, which is due to the lack of cooperative relations with related agencies, academics, business people, communities, and local media in building and developing tourist attractions, and the lack of community participation in developing tourist attractions. This research uses a qualitative method with a descriptive approach through SWOT analysis with the Penthahelix Model to describe the situation in the field which is then examined to find general problem solving. The purpose of this research is to find out the extent to which Stakeholders (Academics, Business Actors, Communities, Government and Media) participate in the development of tourism in the district of Centralapanuli especially on Kalimantung Island and Mursala Island along with phenomena that describe the obstacles faced and efforts to overcome obstacles.